Preoperative topical testosterone for penile hypospadias repair `a comparative study` - Islam Mahmoud Wali; Amr Abdelhamid AbouZeid; Nehal Ahmed Radwan; Mohamed Abdel Sattar GadAllah; Wael Ahmed Ghanem; Osama El-Naggar (SpringerOpen, 2020)
Abstract Background Although the outcome of hypospadias repair has much improved, repair of a small-sized phallus is still challenging. Whether preoperative hormonal therapy is beneficial remains controversial. In this report, we prospectively conducted a clinical trial comparing two groups of patients regarding the effect of preoperative topical testosterone application on the outcome of primary hypospadias repair. Results The study included 40 cases of primary hypospadias with a small glans. Their age ranged from 6 months to 3 years. Patients were divided into two equal groups. Group A were treated by local application of testosterone topical gel 1% for 30-40 days and stopped one month before operation, while cases in group B did not receive preoperative hormonal treatment. Genital skin biopsies were taken for histopathological examination. For group A, penile measurements were documented before and after hormonal therapy. There was a significant increase in all penile parameters after hormonal stimulation in group A. Interestingly, the ventral penile length proximal to the meatus showed more growth in response to hormonal stimulation compared to ventral penile length distal to meatus. We did not find significant difference between both groups regarding the rate of postoperative complications. Also, the cosmesis and parent satisfaction were 'more or less' similar. On the histopathological level, we could not detect a difference between both groups regarding micro-vessel density using CD31, which is a vascular marker indicating neovascularization supposed to play a fundamental role in the healing process. Conclusion The use of preoperative topical testosterone significantly increases the size of the hypospadiac phallus. However, this increase in size appears to be disproportionate on the ventral penile surface and has not been reflected on improving the surgical outcome. Level of evidence This is a case control study (level III evidence).